Subject-specific quality profiles of spelling instruction in Germany and Switzerland - Wiprächtiger, Maja; Stahns, Ruven; Schurig, Michael; Riegler, Susanne; Harcsa, Romana (Swiss Journal of Educational Research, 2023)
As part of the cross-national comparative study "Profess-R", 43 spelling lessons on double consonant spelling in grades 3 to 6 were videotaped and evaluated with regard to their subject-specific quality. The article describes which dimensions were used to assess the subject-specific quality of spelling lessons and reports on the findings gained by means of rating on the quality of the observed lessons in Germany and Switzerland. Using cluster procedures, three subject-specific quality profiles of spelling instruction can be identified, which differ significantly in the expression of the examined quality characteristics.